The Sayers Swindle - Abbott, Victoria (Abbott, Victoria. Book collector mystery., 2013)
A follow-up to The Christie Curse finds Jordan Bingham tracking down a missing set of valuable Dorothy Sayers first-edition novels and preparing to make a strategic trade with an elderly man whose entire family disappears at the same time a murdered body is discovered.